Cooperative backhaul sharing and caching for home cells. (July 2017) - Khan, Muhammad Asad; Leng, Supeng; Min, Geyong; Huang, Xiaoyan; Qiao, Guanhua
Abstract: In this paper, we present a cooperative small cell architecture that improves the performance of home-based femto cells by sharing the backhaul resources and cooperative caching of multimedia contents. Particularly, backhaul resource sharing attempts to utilize the surplus bandwidth in neighboring home cells to satisfy user demand. Based on the Max-Min Fair (MMF) principle, we formulate the optimization problem to minimize the gap between demand and available resources. Furthermore, we present a cooperative distributed caching scheme, in which the caches of all home cells and the gateway can be treated as a single cooperative cache. The data items are locally cached without redundancy in order to maximize the local content hit ratios and reduce the overall packet delivery delay in the network. Simulation results indicate that our model significantly improves the user satisfaction level by bandwidth sharing and reducing the system delay.